Global landform and lithology class at 250 m based on the USGS global ecosystem map - Hengl, Tomislav (Zenodo, 2018)
Layers include: lithology (15) and landform (7) indicator maps (0-100%). Derived from the USGS Global Ecosystem Map, i.e. the EcoTapestry map. Water bodies masked out. Antarctica is not included. To access and visualize maps use: OpenLandMap.org If you discover a bug, artifact or inconsistency in the maps, or if you have a question please use some of the following channels: Technical issues and questions about the code: https://gitlab.com/openlandmap/global-layers/issues General questions and comments: https://disqus.com/home/forums/landgis/ All files internally compressed using "COMPRESS=DEFLATE" creation option in GDAL. File naming convention: dtm = theme: digital terrain models / relief and soil, lithology = variable: lithological class, usgs.ecotapestry = determination method: USGS Global Ecosystem Map, p = probability 0-100%, 250m = spatial resolution / block support: 1 km, s0..0cm = vertical reference: land surface, 2014 = time reference: year 2014, v1.0 = version number: 1.0, : {"references": ["Sayre, R., J. Dangermond, C. Frye, R. Vaughan, P. Aniello, S. Breyer, D. Cribbs, D. Hopkins, R. Nauman, W. Derrenbacher, D.Wright, C. Brown, C. Convis, J. Smith, L. Benson, D. Paco VanSistine, H. Warner, J. Cress, J. Danielson, S. Hamann, T. Cecere, A. Reddy, D. Burton, A. Grosse, D. True, M. Metzger, J. Hartmann, N. Moosdorf, H. D\u00fcrr, M. Paganini, P. DeFourny, O. Arino, S. Maynard, M. Anderson, and P. Comer, 2014, A New Map of Global Ecological Land Units \u2013 An Ecophysiographic Stratification Approach. Washington, DC: Association of American Geographers. 46 pages.", "Hartmann, J., & Moosdorf, N. (2012). The new global lithological map database GLiM: A representation of rock properties at the Earth surface. Geochemistry, Geophysics, Geosystems, 13(12)."]}